Association of HCV Prior Infection and Unprotected Sex on Subsequent HIV Acquisition Risk in the Era of Treatment as Prevention - Fangfang Chen; Houlin Tang; Juan Han; Dongmin Li; Peilong Li; Ning Wang; Mengjie Han; Lan Wang; Lu Wang (Frontiers in Medicine, 2022)
BackgroundsLittle was known about the impact of HCV prior infection on HIV transmission and acquisition. We aimed to explore whether HCV prior infection and its interactions with unprotected sex affected HIV acquisition.MethodsThis study was conducted among HIV heterosexual serodiscordant couples whose index cases were receiving treatment during 2008–2014 in Zhumadian. At baseline, we collected information on demographics and medical history of ART use, CD4 count, and HIV viral load for index partners, and also HIV and HCV status for non-index partners. For each year's visit, we followed up on sexual behaviors among couples in the recent year and HIV seroconversion of non-index partners. Analyses of the Cox model and synergistic interaction were performed.ResultsWe identified 81 HIV seroconversions over 18,370.39 person-years, with the overall HIV seroconversion rate of 0.44 per 100 person-years. Couples, whose index cases were aged 50 years and above, had a baseline viral load >400 copies per ml and no AIDS-defining illness, and newly-initiated ART in the study period had a higher risk of HIV seroconversion. Unprotected sex and HCV prior infection showed a synergistic association with HIV acquisition risk (RERI = 3.65, SI = 0.48, AP = 2.24).ConclusionUnprotected sex and HCV infection were independent risk factors associated with HIV acquisition. The coexistence of them might have a synergistic effect on the risk which needs further research.